2010
DOI: 10.1017/s0007114510000747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple-micronutrient supplementation on maternal nutrient status, infant birth weight and gestational age at birth in a low-income, multi-ethnic population

Abstract: Poor nutrient intake during pregnancy can adversely affect both infant and maternal health. The aim was to investigate the efficacy of multiple-micronutrient supplementation during pregnancy in a socially deprived population in the developed world. We conducted a randomised, double-blind, placebo-controlled trial of multiple-micronutrient supplementation including 20 mg Fe and 400 mg folic acid, from the first trimester of pregnancy in 402 mothers, in East London, UK. Nutrient status was measured at recruitmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 23 publications
6
62
1
14
Order By: Relevance
“…A decrease in ferritin concentration regardless of supplementation with iron has been observed in other studies (2729). Plasma volume expansion and subsequent hemodilution may explain the lower ferritin concentrations in late pregnancy.…”
Section: Discussionsupporting
confidence: 79%
“…A decrease in ferritin concentration regardless of supplementation with iron has been observed in other studies (2729). Plasma volume expansion and subsequent hemodilution may explain the lower ferritin concentrations in late pregnancy.…”
Section: Discussionsupporting
confidence: 79%
“…Results show positive associations with birthweight and head circumference. [9][10][11][12] This substantiates our positive association between embryonic size and RBC folate up to 1812 nmol/l, as the previously reported levels of first-trimester RBC folate were below this level. Only Takimoto et al 23 have reported a high first-trimester mean RBC folate of 1317 nmol/l (SD, 824 nmol/l), but they observed no associations with birthweight or head circumference, which may be because of the small sample size (n = 51) and the performance of continuous rather than stratified analysis for different cut-offs for RBC folate.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with prior literature, women who reported taking prenatal vitamins weekly or every day had higher folate concentrations than women who reported rarely or never consuming prenatal vitamins. 41,42 In addition, women who reported adequate food security and frequent consumption of fresh fruits and vegetables had higher whole blood folate and lower serum cotinine concentrations. Associations between covariates and whole blood 5-methyltetrahydrofolate levels were similar to those observed for whole blood folate levels (Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%